Major Pettigrew's last stand - Simonson, Helen (Bloomsbury, 2010)
An enchanting, humorous and heart-warming novel set in an English village A Richard & Judy Book Club selection Major Ernest Pettigrew is perfectly content to lead a quiet life in the sleepy village of Edgecombe St Mary, away from the meddling of the locals and his overbearing son. But when his brother dies, the Major finds himself seeking companionship with the village shopkeeper, Mrs Ali. Drawn together by a love of books and the loss of their partners, they are soon forced to contend with irate relatives and gossiping villagers. The perfect gentleman, but the most unlikely hero, the Major must ask himself what matters most: family obligation, tradition or love? Funny, comforting and heart-warming, Major Pettigrew's Last Stand proves that sometimes, against all odds, life does give you a second chance.